Antona Czechowa myślenie o człowieku w opowiadaniu Student - Macheta, Lidia (Slavia Orientalis, 2025)
The article examines the specificity of Chekhov's thinking about man as revealed in The Student. The main goal of these analyses is to confirm the hypothesis that this form of thinking is ontological in nature – it concerns the issue of one becoming oneself (humanization). The analyses are carried out at the level of ontological anthropology, which examines man from the perspective of the possibilities and obligations of being oneself. The truthfulness of the hypothesis thus put forward is confirmed in relation to a contemporary concept of philosophy, called practical philosophy, as developed mainly by Pierre Hadot in relation to ancient philosophy, as well as to philosophy as such in general, and which falls within the trend of onto-anthropological thinking about man. On the basis of this concept, philosophy is understood not as a theory, but as "spirituality", an existential attitude, a method of changing the relation to reality and transforming human existence; this concept is chosen mainly because it considers the idea of becoming oneself in the sphere of existence and focuses on ancient philosophy, which Chekhov knew and appreciated, inspired especially by the philosophy of Marcus Aurelius, a representative of stoicism, considered as an exemplary figure of "philosophical spirituality".